Book Reviews / Rezensionen - Massimo Cingolani (Intervention. European Journal of Economics and Economic Policies, 2012)
Books reviewed: Claude Gnos, Louis-Philippe Rochon (eds.) (2011): Credit, Money and Macroeconomic Policy. A Post-Keynesian Approach, Cheltenham, UK
Keywords: 330